Skrining Salinitas Padi Mutan Insersi Pembawa Activation-Tagging pada Fase Perkecambahan - Zannati, Anky; Widyastuti, Utut; Nugroho, Satya (Jurnal Penelitian Pertanian Tanaman Pangan, 2015)
Insert mutation is a method in the functional genomics analysis, using Ac and Ds transposable elements that capable of transposing genes in plant genome, including rice. Using such method, it is possible to identify functional genes, such as abiotic stress tolerance genes in rice plant. The objectives of this research were to screen activated-tag mutant rice for tolerance to salinity stress. Seventy-five lines were chosen from a 1,000 fast screeningexperiment to identify mutant responsive to salinity stress. The mutant was validated in three screening batches (A, B and C) at germinating stage in Yoshida solution containing 200g/L NaCl. Three potential tolerant mutants, with the highest vigor index were identified from each batch. Insertion analysis of the nine mutants showed that the activator/dissociation (Ac/Ds) elements were still present in the genome, based on the bar and hpt marker genes as identified from the positive PCR.